Is Physical Intimate Partner Violence a Risk Factor for Physical Child Maltreatment in a Nationally Representative Sample of Finnish School Children? - Mielityinen, Laura Annika (Journal of interpersonal violence, 2025)
Previous studies have found a high co-occurrence between intimate partner violence and child maltreatment. However, little is known about the nuanced association between physical intimate partner violence (pIPV) and physical child maltreatment (pCM) in countries where corporal punishment is prohibited by law. Furthermore, there is a lack of information on the co-occurrence from children’s perspectives and nationally representative surveys. The main objective of this study was to examine the connection between pIPV and pCM in a nationally representative sample of 12 to 13 and 15- to 16-year-old Finnish children (N = 6,825) after controlling for other known risk factors. The χ2 test and the logistic regression model were used. Around 47.3% of the children who had been exposed to pIPV had also experienced pCM during the past year, whereas 6.7% of those who had not been exposed to pIPV reported pCM. Children exposed to pIPV were almost three times more likely to experience pCM than children who were not exposed to pIPV. The connection remained statistically significant after controlling for other risk factors. Prevention and early identification of pIPV might reduce pCM in families. Targeted prevention efforts and interventions aimed at physical family violence are necessary to reduce its occurrence and mitigate the impact of abuse on children and families.